2014
DOI: 10.1007/s10336-014-1056-6
|View full text |Cite
|
Sign up to set email alerts
|

Shifting to an energy-poor diet for nitrogen? Not the case for wintering herbivorous Lesser White-fronted Geese in China

Abstract: Geese often forage on mid-winter foods that fail to satisfy daily energy needs, but they may do so to acquire other nutrients, such as nitrogen. We tested this hypothesis by evaluating nitrogen budgets, namely the balance of nitrogen income against expenditure, of wintering Lesser White-fronted Geese Anser erythropus feeding at two sites within East Dongting Lake, China, where they could and could not balance daily energy budgets. Geese could balance nitrogen budgets in energy-rich habitats but were less able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the early winter, the Greater White-fronted Goose needs plenty of food resources to make up for the energy loss in the process of migration and a large amount of time is consequently spent foraging in the meadows. In the middle of the winter period, the Carex entered the mature stage, with a low protein and high cellulose content, in order to make up the energy balance (Wang et al 2014), and the geese moved to the paddy fields where they spent a large amount of time foraging. The time budget of the movement is related to the food resources in various habitats at Shengjin Lake (Fox et al 1991).…”
Section: Effect Of Food Resources On Activity Time Budgetsmentioning
confidence: 99%
“…In the early winter, the Greater White-fronted Goose needs plenty of food resources to make up for the energy loss in the process of migration and a large amount of time is consequently spent foraging in the meadows. In the middle of the winter period, the Carex entered the mature stage, with a low protein and high cellulose content, in order to make up the energy balance (Wang et al 2014), and the geese moved to the paddy fields where they spent a large amount of time foraging. The time budget of the movement is related to the food resources in various habitats at Shengjin Lake (Fox et al 1991).…”
Section: Effect Of Food Resources On Activity Time Budgetsmentioning
confidence: 99%
“…Invasion of smooth cordgrass Spartina alterniflora greatly affected species composition and structure of bird communities at the Yangtze estuary (Ma et al 2009). Buffalo grazing negatively affected the growth and availability of grass, which may further affect grass-feeding waterbirds (Kang 2005, Wang et al 2014). Nevertheless, some researchers suggested that buffalo grazing can assist in maintaining suitable grass heights for waterbirds (Zhao et al 2012).…”
Section: Possible Influencing Factors From the Floodplainmentioning
confidence: 99%
“…Food quality plays an important role in food selection of animals (Ely & Raveling, 2011; Klaassen & Nolet, 2008). Birds generally select foods high in energy content and protein but low in fibre (Nolet et al, 2002; Wang et al, 2014). Vallisneria tubers contain a level of energy similar to Carex and other grassland plants, but are lower in fibre and ash (Burnham et al, 2017; Zhang & Lu, 1999).…”
Section: Discussionmentioning
confidence: 99%